2007
DOI: 10.1152/ajpcell.00270.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electron transport protects cardiac mitochondria and decreases myocardial injury during ischemia and reperfusion

Abstract: Chen Q, Camara AK, Stowe DF, Hoppel CL, Lesnefsky EJ. Modulation of electron transport protects cardiac mitochondria and decreases myocardial injury during ischemia and reperfusion. Am J Physiol Cell Physiol 292: C137-C147, 2007. First published September 13, 2006; doi:10.1152/ajpcell.00270.2006.-Mitochondria are increasingly recognized as lynchpins in the evolution of cardiac injury during ischemia and reperfusion. This review addresses the emerging concept that modulation of mitochondrial respiration during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
240
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(256 citation statements)
references
References 140 publications
12
240
1
3
Order By: Relevance
“…In contrast, the treatment of isolated, perfused rabbit heart with rotenone (mitochondrial complex I inhibitor) decreased the production of ROS in mitochondria and preserved the contents of cardiolipin and cytochrome c measured after 45 min of ischemia (Chen et al, 2007). Interestingly, in isolated rat cardiocytes, antimycin A-caused ROS production was abolished by the mitochondrial uncoupler (Kabir et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the treatment of isolated, perfused rabbit heart with rotenone (mitochondrial complex I inhibitor) decreased the production of ROS in mitochondria and preserved the contents of cardiolipin and cytochrome c measured after 45 min of ischemia (Chen et al, 2007). Interestingly, in isolated rat cardiocytes, antimycin A-caused ROS production was abolished by the mitochondrial uncoupler (Kabir et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some inhibition of mitochondrial respiration observed at the highest CE concentration can be beneficial in some circumstances and may complement the effect of uncoupling. The blockade of electron transport and the partial uncoupling of respiration were regarded as two mechanisms whereby manipulation of mitochondrial metabolism during ischemia decreases cardiac injury (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been shown that complex I inhibition may underlie the cardioprotective effects of agents such as amobarbital [29,30], volatile anesthetics [60], and ranolazine [61]. Complex II inhibitors such as diazoxide [60] and 3-nitropropionic acid [62,63] are also cardioprotective, as are complex IV inhibitors such as hydrogen sulfide [64,65] and carbon monoxide [66].…”
Section: Discussionmentioning
confidence: 99%
“…Considering several reports of reversible complex I inhibition by S-nitrosation [27,28,47,48], with the recent finding that complex I inhibition is cardioprotective [29,30], and the known importance of NO • in IPC [16], we hypothesized that complex I S-nitrosation may be an endogenous cardioprotective mechanism [27]. While ischemic conditions (acidic pH) can favor SNO formation from nitrite [21,50], and hypoxia has been proposed to enhance complex I Snitrosation [51], it is known that typical laboratory lighting conditions can degrade SNOs.…”
Section: Preservation Of Endogenous Sno Correlates With Cardioprotectionmentioning
confidence: 99%
See 1 more Smart Citation